Stress Spectrum in Pregnancy: Association with Socio-Economic, Educational, and Cultural Factors - N. Masiukovichi; E. Nikoleishvili; W.M. Caudle (European Scientific Journal, ESJ, 2025)
Introduction: The multifaceted nature of stress during pregnancy is known to influence maternal health, pregnancy outcomes, and fetal development. Objective: This study aims to explore the association between stress during pregnancy and socio-economic, educational, and cultural factors in Tbilisi, Georgia. Methods: A cross-sectional study was conducted among 398 pregnant women in Tbilisi, Georgia, utilizing a pregnancy-specific questionnaire approved by the University of Georgia's ethics board. Saliva cortisol levels were measured in a focus group of 95 pregnant women who self-reported stress. Statistical analysis was performed using SPSSv.23.0.  Results: Two groups were identified: Group I (n = 172), comprising women who self-reported stress and had elevated cortisol levels (n = 95), and Group II (n = 226), who did not report stress. In Group I, saliva cortisol levels indicated mild stress in 30.5%, moderate stress in 34.7%, and high stress in 34.7%. Occupational stress factors were more prominent in Group I compared to Group II: job-related stress (OR = 1.59, p = 0.02, CI = 95%), overtime work (OR = 3.05, p = 0.001, CI = 95%), and continued work throughout pregnancy (OR = 1.82, p = 0.01, CI = 95%). Environmental stress was more prevalent among women living alone or with a partner (OR = 1.59, p = 0.03, CI = 95%). Relationship stress was significantly lower in Group I (p = 0.01), while psychological stress, such as spontaneous abortion, was higher (OR = 2.19, p = 0.001, CI = 95%). Educational levels did not differ significantly between groups. Conclusions: Self-reported stress is closely linked to elevated cortisol levels during pregnancy. Findings highlight the importance of addressing psychological, social, and occupational factors in prenatal care, to address the improvement of maternal and fetal health outcomes in the future.